The Effectiveness of Clinical Pharmacist Intervention in Reducing Drug Related Problems of Childhood Acute Lymphoblastic Leukemia Patient in Tangerang District General Hospital, Indonesia - Budiastuti, Rizky Farmasita; Radji, Maksum; Purnamasari, Rini (UI Scholars Hub, 2019)
This study aimed to evaluate the clinical pharmacist interventions in reducing drug-related problems (DRPs) in childhood acute lymphoblastic leukemia (ALL) patients in the Tangerang District General Hospital, Banten, Indonesia. This study used a prospective analysis of patients with a pre-post design between January-March 2017. The Pharmaceutical Care Network Europe (PCNE) (V6.2) pre-post study system was used to identify the DRPs of 138 patients. The Pharmacist interventions were addressed to physicians, patients, and other health professions to determine the effectiveness of pharmacist interventions before and after the intervention. The number of identified DRPs was 177 problems and the identified types of DRP was 164 types. The pharmacist interventions significantly decreased the DRPs from 177 to 10 DRPs (p < 0.05) and type of DRPs from 164 to 10 types of DRPs (p < 0.05). Risk factors for nutritional status, type of ALL, comorbidities, number of drug items, and type of treatments did not significantly affect (p > 0.05) to the decreased of the number and type of DRPs. Clinical pharmacist interventions able to reduce the number and type of DRPs and can improve treatment outcomes in childhood ALL.